Upper extremity disorders in heavy industry workers in Greece - Tsouvaltzidou, Thomaella (World J Orthop, 2017)
AIM: To investigate the disability due to musculoskeletal disorders of the upper extremities in heavy industry workers. METHODS: The population under study consisted of 802 employees, both white- and blue-collar, working in a shipyard industry in Athens, Greece. Data were collected through the distribution of questionnaires and the recording of individual and job-related characteristics during the period 2006-2009. The questionnaires used were the Quick Disabilities of the Arm, Shoulder and Hand (QD) Outcome Measure, the Work Ability Index (WAI) and the Short-Form-36 (SF-36) Health Survey. The QD was divided into three parameters - movement restrictions in everyday activities, work and sports/music activities - and the SF-36 into two items, physical and emotional. Multiple linear regression analysis was performed by means of the SPSS v.22 for Windows Statistical Package. RESULTS: The answers given by the participants for the QD did not reveal great discomfort regarding the execution of manual tasks, with the majority of the participants scoring under 5%, meaning no disability. After conducting multiple linear regression, age revealed a positive association with the parameter of restrictions in everyday activities (b = 0.64, P = 0.000). Basic education showed a statistically significant association regarding restrictions during leisure activities, with b = 2.140 (P = 0.029) for compulsory education graduates. WAI’s final score displayed negative charging in the regression analysis of all three parameters, with b = -0.142 (P = 0.0), b = -0.099 (P = 0.055) and b = -0.376 (P = 0.001) respectively, while the physical and emotional components of SF-36 associated with movement restrictions only in daily activities and work. The participants’ specialty made no statistically significant associations with any of the three parameters of the QD. CONCLUSION: Increased musculoskeletal disorders of the upper extremity are associated with older age, lower basic education and physical and mental/emotional health and reduced working ability.